2002
DOI: 10.1080/1028415021000033820
|View full text |Cite
|
Sign up to set email alerts
|

Nefazodone Alters NPY Immunostaining in Rat Arcuate-paraventricular Projection without Changes in Food Intake and Body Weight

Abstract: Nefazodone is an antidepressant drug that inhibits serotonin and noradrenaline reuptake. The aim of the present work was to study the effects of nefazodone on food intake, body weight, adiposity and hypothalamic NPY immunostaining in rats. For this purpose, male Sprague-Dawley rats (3-month-old) were administered with nefazodone (20 mg/kg; i.p) daily for two weeks. The control group was given 0.9% NaCl solution. Hypothalamic arcuate, paraventricular, periventricular, supraoptic and suprachiasmatic nuclei and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…This suggestion is strengthened by the report of Dryden et al (52) who reported that treatment with fluoxetine, a specific serotonin reuptake inhibitor, reduced NPY concentrations in the PVN without changes of mRNA levels in the ARC. Another study also reported that a significant decrease in NPY immunostaining in the PVN, but not in the arcuate or suprachiasmatic nuclei, was observed after treatment with nefazodone, serotonin, and noradrenaline reuptake inhibitor (53). Accordingly, our results suggest that the anorexigenic effect of CS in HF diet-induced obese rats may be, in part, mediated through the NPY ARC-PVN projection.…”
Section: Discussionsupporting
confidence: 47%
“…This suggestion is strengthened by the report of Dryden et al (52) who reported that treatment with fluoxetine, a specific serotonin reuptake inhibitor, reduced NPY concentrations in the PVN without changes of mRNA levels in the ARC. Another study also reported that a significant decrease in NPY immunostaining in the PVN, but not in the arcuate or suprachiasmatic nuclei, was observed after treatment with nefazodone, serotonin, and noradrenaline reuptake inhibitor (53). Accordingly, our results suggest that the anorexigenic effect of CS in HF diet-induced obese rats may be, in part, mediated through the NPY ARC-PVN projection.…”
Section: Discussionsupporting
confidence: 47%
“…In addition to the effect of 5‐HT on the firing rate, it is known that modulation of 5‐HT and NPY itself can affect SCN function (Palus et al, 2013; Smith et al, 2015). For example, previous studies have shown that chronic SSRIs administration in adult male rats induces a reduction in NPY expression in the paraventricular nucleus and lateral hypothalamic area but not in the SCN specifically (Gutiérrez et al, 2002; Saracíbar et al, 2002). Furthermore, Ugrumov et al (1994) showed that the treatment with serotonergic agonists modulates the differentiation of peptidergic neurons in SCN, even before the establishment of afferent inputs from RN during the prenatal development period.…”
Section: Discussionmentioning
confidence: 99%